Extracts of Physalis peruviana Protect Astrocytic Cells Under Oxidative Stress With Rotenone - Areiza-Mazo, Natalia; Robles, Jorge; Zamudio-Rodriguez, Jairo A.; Giraldez, Lisandro; Echeverria, Valentina; Barrera-Bailon, Biviana; Aliev, Gjumrakch; Sahebkar, Amirhossein; Ashraf, Ghulam Md; Barreto, George E. (Frontiers in Chemistry, 2018)
The use of medicinal plants to counteract the oxidative damage in neurodegenerative diseases has steadily increased over the last few years. However, the rationale of for using these natural compounds and their therapeutic benefit are not well explored. In this study, we evaluated the effect of different Physalis peruviana extracts on astrocytic cells (T98G) subjected to oxidative damage induced by rotenone. Different polarityE extracts of fresh and dehydrated fruits of the plant with different polarities were preparedobtained and tested in vitro. Our results demonstrated that the ethanolic extract of fresh fruits (EF) and acetone-dehydrated fruit extract acetone (AD) increased cell viability, reduced the formation of reactive oxygen species (ROS) and preserved mitochondrial membrane potential. In contrast, we observed a significant reduction in mitochondrial mass when rotenone-treated cells were co-treatedadministered with EF andor AD. These effects were accompanied by a reduction in the percentage of cells with fragmented/condensed nuclei and increased expression of endogenous antioxidant defense survival proteins such as ERK1/2. In conclusion, our findings suggest that ethanolic and acetone extracts from Physalis P. peruviana are potential medicinal plant extracts to overcome oxidative damage induced by neurotoxic compounds.